1983
DOI: 10.1039/dt9830001417
|View full text |Cite
|
Sign up to set email alerts
|

Organic chemistry of dinuclear metal centres. Part 3. µ-Carbene complexes of iron and ruthenium from alkynes viaµ-vinyl cations

Abstract: Protonation of the complexes [M2(CO)(p-CO){p-C(0)C2R2)(q-C5H5)2] [M = Fe or Ru; R2 = H2, Ph, , H (Me), or H (Ph)] with H BF,*OEt, results in rapid carbon-carbon bond cleavage and formation of the p-vinyl cations [M2(CO)2(p-CO){p-C(R)=C(H)R)(q-C5H5)2] +, containing a cis arrangement of R groups. Addition of HBF,*OEt2 to [Ru,(CO) (p-CO){p-C(0)C2Me2}(q-C5H5)2] produces the cation [Ru2(CO) (p-CO)({p-C(H)(O)C,Me,)(q-C,H,),] +, which isomerises slowly to [ R u ~( C O ) ~( ~-C O ) { ~-C ( M ~) = C ( H ) M ~) ( ~-C ~H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 2 publications
4
42
0
Order By: Relevance
“…No coupling was resolved between the geminal vinyl protons. This correlates with other l-CR=CH 2 vinyl ligands for which negligible, or only a small coupling is observed [22][23][24][25][26][27][28]. The CH 2 protons of the lactone ring are observed as multiplets at d 4.32 and 4.18 with a geminal H-H coupling of 14 Hz and smaller unresolved coupling to both phosphorus atoms.…”
Section: Introductionsupporting
confidence: 54%
“…No coupling was resolved between the geminal vinyl protons. This correlates with other l-CR=CH 2 vinyl ligands for which negligible, or only a small coupling is observed [22][23][24][25][26][27][28]. The CH 2 protons of the lactone ring are observed as multiplets at d 4.32 and 4.18 with a geminal H-H coupling of 14 Hz and smaller unresolved coupling to both phosphorus atoms.…”
Section: Introductionsupporting
confidence: 54%
“…Adams and Cotton put forward a mechanism for the cis-trans isomerization of [Fe 2 (l-CO) 2 (CO) 2 (Cp) 2 ] which is now a textbook example of the dynamic behaviour of metal carbonyl compounds [7] and cis-trans interconversion has been investigated in other related dinuclear complexes with lalkylidenes [8], l-CNR [9], and l-vinyl [10].…”
Section: Insertion Of Symmetrically-disubstituted Alkynesmentioning
confidence: 99%
“…6, 133.5, 130.2, 129.9, 129.4 5H,Ph);5.76,5.43,5.01,4.39 (d,2H,2 J HH ¼ 15 Hz,CH 2 Ph);5.32,5.28,5.26,5.21 (s,10H,Cp); 4.14, 3.91, 3.86 (s, 6H, CO 2 Me); 3.77, 3.05 (s, 3H, NMe); (E:Z ratio ¼ 0.5). 13 Complex 12 has been obtained following the same procedure described for the synthesis of 10 .51 (s, 10H, Cp); 3.94 (t, 2H, 3 J HH ¼ 9 Hz, C c -CH 2 ); 3.85, 3.32 (s, 6H, NMe); 2.03 (m, 2H, C c -CH 2 CH 2 ); 1.92 (s, 3H, C b Me); 1.28 (t, 3H, 3 J HH ¼ 7 Hz, 3H, C c -CH 2 CH 2 CH 3 ). 13 C NMR (CDCl 3 ) d 255.1 (l-CO); 225.7 (C a ); 210.1 (CO); 201.9 (C c ); 90.4, 87.9 (Cp); 68.5 (C b ); 52.4 (C c -CH 2 ); 49.5,45.4 (NMe); 32.8 (C c -CH 2 CH 2 ); 14.7, 14.6 (C c -CH 2 CH 2 CH 3 and C b Me).…”
Section: Syntheses Of [Fementioning
confidence: 99%
“…In particular, Knox and co-workers have shown that for complexes 4 the onset of vinyl oscillation for the iron complex is around 50°C, whereas the analagous ruthenium complex is static at this temperature (18). Following this trend, the lack of fluxionality of complex 3 is not that surprising.…”
Section: Synthesesmentioning
confidence: 82%
“…Structure factor amplitudes are no longer being deposited and may be obtained directly from the author lation between two metal centers is well known (23) and renders numerous p-alkenyl complexes fluxional, the energetics of the process are both substituent (18, 19a) and metal dependent (18). In particular, Knox and co-workers have shown that for complexes 4 the onset of vinyl oscillation for the iron complex is around 50°C, whereas the analagous ruthenium complex is static at this temperature (18).…”
Section: Synthesesmentioning
confidence: 99%